2022
DOI: 10.15391/snsv.2022-2.005
|View full text |Cite
|
Sign up to set email alerts
|

Features of the development of strength training of highly qualified football referees in the competitive period

Abstract: Purpose: to identify the features of the development of strength training of highly qualified football referees in the competitive period. Material & Methods: the study involved 30 highly qualified football referees aged 35-42: 4 FIFA referees, 15 Premier League referees and 11 First League referees. Results: the training program for strength development in the competitive period included new fitness training tools using TRX® functional loops, step platform, BOSU hemisphere, 6D sliding. In the preparator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…Subsequently, it was observed how specific strength and speed training was related to decision making (percentage of success), which was related to the physical condition (experiment 2). For all these reasons, these results showed that physical qualities, specifically those linked to strength and speed, moderated the behavior of the SR and could be decisive in general preparation, as has been shown in previous studies [ 26 ]. In this sense, these findings seem decisive in SRs committees and are keys when it comes to promoting or keeping SRs.…”
Section: Discussionsupporting
confidence: 80%
“…Subsequently, it was observed how specific strength and speed training was related to decision making (percentage of success), which was related to the physical condition (experiment 2). For all these reasons, these results showed that physical qualities, specifically those linked to strength and speed, moderated the behavior of the SR and could be decisive in general preparation, as has been shown in previous studies [ 26 ]. In this sense, these findings seem decisive in SRs committees and are keys when it comes to promoting or keeping SRs.…”
Section: Discussionsupporting
confidence: 80%